Imaginary irishness: the feminine in dramatisations of the Paster Rising in Sean O’Casey’s the plough and the stars and Tom Murphy’s The Patriot Game - Parra, Cláudia [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Ireland’s particular national culture has shaped an imaginary conception of identity which has also affected the image of women. Irish drama has contributed significantly to the debate on and revisionism of Irish identity and, in the twentieth century, the Easter Rising in 1916 was chosen by some Irish playwrights as a background to promote reflection on this question. Sean O’Casey and Tom Murphy presented versions of the Easter Rising on the Abbey stage which approached the identity of Irish women in a nationalistic context. A comparison of these two dramatic texts reveals that, although the playwrights used different strategies, they both reassessed the female image promoted by Irish nationalism.

Uma vez que a cultura nacional irlandesa tem formado uma concepção imaginária de identidade, isso afeta também a imagem da mulher. O drama irlandês tem contribuído muito para o debate e revisionismo sobre a identidade irlandesa e, no século XX, a Revolta da Páscoa em 1916 foi escolhida como contexto por alguns dramaturgos irlandeses pra promover uma reflexão sobre essa questão. Sean O’Casey e Tom Murphy apresentaram versões da Revolta da Páscoa nos palcos do Abbey que abordaram a identidade da mulher irlandesa em um contexto nacionalista. Uma comparação desses dois textos dramáticos revela que, embora os dramaturgos tenham usado estratégias diferentes, ambos reavaliaram a imagem feminina promovida pelo nacionalismo irlandês.
Irlandesidade imaginária: o feminino em dramatizações do Levante de Páscoa em The Plough and the Stars, de Sean O'Casey e The Patriot Game, de Tom Murphy
Keywords: Sean O’Casey; Tom Murphy; Revolta da Páscoa; Teatro Irlandês; Identidade feminina; Easter Rising; Irish Drama; Female Identity